The Implementation of Professional Competence in Teaching ESP at Four Private Vocational Schools in Grobogan - Rahmatunnisa, Eva; Mujiyanto, Januarius; Linggar Bharati, Dwi Anggani (Universitas Negeri Semarang, 2021)
A Professional teacher should master some competencies; one of them is professional competence. Accordingly, the preliminary research showed that some teachers had problems in the teaching-learning process. This research aimed to analyze the teachers’ competence in designing the syllabus, creating the lesson plan, developing the learning material, applying the learning media, the teaching-learning process, and constructing the students' assessment. This study was a qualitative case study. Subjects of the study were four private vocational school teachers in Grobogan. The data were collected by implementing observation, document analysis, and interviews. There were three steps in analyzing data, such as identifying, analyzing, and interpreting. The result showed that all teachers were good at designing ESP syllabus according to the instructional material, learning activity, assessment, time allocation, and learning resources. Then, they had created an ESP lesson plan well even though a teacher missed writing the learning method and the learning media. The media used were such as whiteboard, board markers, LCD, laptop, and other supporting materials. Additionally, all teachers did the teaching- learning process well despite some teachers found difficulties in applying lesson plan, they could not associate the lesson plan with the real condition in the class. The last finding showed that all teachers made an individual assignment for their students. But there was only a teacher who made group assignments. This research is expected to contribute to the teachers or lecturers in implementing professional competence to teach ESP.